Application of the SCAI classification to admission of patients with cardiogenic shock: Analysis of a tertiary care center in a middle-income country. - Héctor González-Pacheco; Rodrigo Gopar-Nieto; Diego Araiza-Garaygordobil; José Luis Briseño-Cruz; Guering Eid-Lidt; Jorge Arturo Ortega-Hernandez; Daniel Sierra-Lara; Alfredo Altamirano-Castillo; Salvador Mendoza-García; Daniel Manzur-Sandoval; Klayder Melissa Aguilar-Montaño; Heriberto Ontiveros-Mercado; et al. (PLoS ONE, 2022)
Aims The Society of Cardiovascular Angiography and Interventions (SCAI) shock stages have been applied and validated in high-income countries with access to advanced therapies. We applied the SCAI scheme at the time of admission in order to improve the risk stratification for 30-day mortality in a retrospective cohort of patients with STEMI in a middle-income country hospital at admission. Methods This is a retrospective cohort study, we analyzed 7,143 ST-segment elevation myocardial infarction (STEMI) patients. At admission, patients were stratified by the SCAI shock stages. Multivariate analysis was used to assess the association between SCAI shock stages to 30-day mortality. Results The distribution of the patients across SCAI shock stages was 82.2%, 9.3%, 1.2%, 1.5%, and 0.8% to A, B, C, D, and E, respectively. Patients with SCAI stages C, D, and E were more likely to have high-risk features. There was a stepwise significant increase in unadjusted 30-day mortality across the SCAI shock stages (6.3%, 8.4%, 62.4%, 75.2% and 88.3% for A, B, C, D and E, respectively; P < 0.0001, C-statistic, 0.64). A trend toward a lower 30-day survival probability was observed in the patients with advanced CS (30.3, 15.4%, and 8.3%, SCAI shock stages C, D, and E, respectively, Log-rank P-value <0.0001). After multivariable adjustment, SCAI shock stages C, D, and E were independently associated with an increased risk of 30-day death (hazard ratio 1.42 [P = 0.02], 2.30 [P<0.0001], and 3.44 [P<0.0001], respectively). Conclusion The SCAI shock stages applied in patients con STEMI at the time of admission, is a useful tool for risk stratification in patients across the full spectrum of CS and is a predictor of 30-day mortality.